Westward migration of tropical cyclone rapid-intensification over the Northwestern Pacific during short duration El Niño - Yi-Peng Guo (Nature Portfolio, 2018)
El Niño events have important impacts on tropical cyclone activity over the western North Pacific. Here, the authors show that short duration El Niño could significantly shift the tropical cyclone rapid intensification westward by transporting ocean heat energy to the western Pacific.